Synaptophysin Immunoreactivity as Marker for Fetal Hippocampal and Cortical Development - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
Researchers at University of Calgary Faculty of Medicine and Alberta Children's Hospital, Canada, have studied synaptophysin immunoreactivity (sIR) in postmortem sections of 162 normal human fetal and neonatal brains of both sexes from 6 to 41 weeks' gestational age.